2020
DOI: 10.1096/fj.202001389rr
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 27 immune complex altered signaling and transport (ICAST): Novel mechanisms of attenuating inflammation

Abstract: Blood levels of heat shock protein (HSP27) and natural IgG auto-antibodies to HSP27 (AAbs) are higher in healthy controls compared to cardiovascular disease patients. Vaccination of mice with recombinant HSP25 (rHSP25, murine ortholog of human rHSP27) increased AAb levels, attenuated atherogenesis and reduced plaque inflammation and cholesterol content. We sought to determine if the HSP27 immune complex (IC) altered MΦ inflammation signaling (Toll Like Receptor 4; TLR4), and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Indeed, contrary to the expected, the pre-incubation of cells with an anti-GGT antibody amplified the TF procoagulant activity as compared to hrGGT per se. It is known that immunocomplexes can activate TLR4 [ 29 ]. Furthermore, monocytes express neonatal Fc receptor for IgG (FcRn) and Fc gamma receptor (FcγR) families whose activation by single IgG and, to a greater extent, immunocomplexes IgG activates TF gene transcription [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, contrary to the expected, the pre-incubation of cells with an anti-GGT antibody amplified the TF procoagulant activity as compared to hrGGT per se. It is known that immunocomplexes can activate TLR4 [ 29 ]. Furthermore, monocytes express neonatal Fc receptor for IgG (FcRn) and Fc gamma receptor (FcγR) families whose activation by single IgG and, to a greater extent, immunocomplexes IgG activates TF gene transcription [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, Feng et al reported increased levels of sHSP27 in only 10% of CHB patients by proteome analysis [11]. Anti-HSP27-Ab not only is more stable and easily detectable in serum, but also might enhance the function of sHSP27 as an in ammatory modulator [13]. Therefore, anti-HSP27-Ab has recently received growing attention and reported to important role in many diseases such as cardiovascular diseases, obesity, and diabetes [9,15,16].…”
Section: Discussionmentioning
confidence: 89%
“…SHSP27 can evoke immune system reactions, resulting in anti-HSP27 antibody production (Anti-HSP27-Ab) [12]. More importantly, the creation of sHSP27 and anti-HSP27-Ab immune complexes have been reported to enhance the function of sHSP27 by altering the signaling of crucial receptors involved in the in ammatory processes [13]. As antibodies are simply measured by blood tests and are often more stable and easily detectable due to higher concentrations [14], recent studies seek to discover the role of circulating anti-HSP27-Ab in various diseases [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…HSP27 immune complex activates TLR4/NF-κB signaling and increases the level of anti-inflammatory cytokine IL-10 in macrophages. Moreover, HSP27 immune complex reduces form cell formation by inhibiting oxidized low-density lipoprotein (oxLDL) binding to scavenger receptors ( 86 ). In addition, under ER stress, chaperone protein 78 kDa glucose-regulated protein (GRP78) dissociates from ER and moves to the cell surface, resulting in the generation of anti-GRP78 autoantibodies which activate NF-κB and induce the expression of adhesion molecules in human endothelial cells ( 87 ).…”
Section: The Nf-κb and Er Stress In Atherosclerosismentioning
confidence: 99%